Competing Institutional Logics And Teaching Effectiveness In Traditional And Online University Classrooms - Billy R. Brocato; Oi-man Kwok (Journal of Public and Professional Sociology, 2018)
Relying on an institutional logics framework, we use a case study method to investigate competing inter-institutional logics effecting U.S. postsecondary teaching effectiveness ratings in traditional and online courses at a midsize Texas public university. Prior research attributes differences to instructor and student attitudes, performative characteristics, and motivation but few studies have examined evaluation outcomes in light of competing logics that contextualize administrators, faculty, and students’ practices in the qualitatively different classroom settings. Using a multilevel latent factor model, we correlated variances in students’ assessments on key institutional criteria and compare differences in students’ teaching effectiveness ratings between the two settings. We theorized that different neoliberal dispositions emerge from competing institutional logics framing actors' normative assumptions in traditional and online classrooms. The findings indicate that instructors’ significantly lower evaluations in online classes were linked to competing institutional logics affecting actors’ cognitions and practices. Noteworthy was students’ assessments were not gender biased from an institutional logics perspective in either instructional field.